Sosialisasi Pelestarian Aksara Sasak Di Era Digital - Adil, Ahmat; Tajuddin, Muhammad; Anas, Andi Sofyan; Ardi, Raden Fany Printi (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2026)
As one of the local cultural heritages of the Sasak people, the Sasak script holds high historical, linguistic, and cultural identity value. However, in the current digital era, the existence of the Sasak script is increasingly threatened due to the dominant use of the Latin alphabet and the low interest of the younger generation in learning it. Therefore, strategic efforts are needed to preserve the Sasak script through an approach relevant to technological developments. This study aims to socialize the preservation of the Sasak script by utilizing digital media as a means of education and information dissemination. The methods used include counseling activities, training, and the use of digital platforms such as social media and interactive learning applications. The results of the activity indicate that the use of digital technology can enrich the knowledge and interest of the community, especially the younger generation, in learning the Sasak script. Thus, the integration of cultural preservation and digital technology is a very effective step to ensure that the Sasak script does not disappear amidst the current of modernization. The results of the evaluation involving 30 respondents showed that the majority of participants gave a positive assessment of the educational game used. The aspect with the highest score was System Integration, with a score of 96.67%, indicating that the system is running well and is optimally integrated. Furthermore, the Art and Aesthetics aspect received the second highest score, at 90%. Therefore, it can be concluded that the use of educational game-based digital media is considered effective, engaging, and beneficial in supporting the learning process and preserving the Sasak script.